ANALISIS MANAJEMEN PEMASARAN DIGITAL BERBASIS E- COMMERCE - Laksmono, Rendro; Dimyati; Munir, Abdul Razak; Artino, Adi; Arief, Syarifuddin (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze e-commerce-based digital marketing management and identify strategies, implementation, and challenges faced by businesses in improving marketing performance. The research method used is a qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation. Informants in this study were business owners who actively utilize e-commerce platforms as a digital marketing tool. The results show that e-commerce-based digital marketing has a positive impact on increasing market reach and sales. Business owners have utilized various e-commerce features such as promotions, discounts, and social media integration to attract consumers. However, marketing strategy planning remains suboptimal due to a lack of analytical data and in-depth market segmentation. Furthermore, customer relationship management remains rudimentary and has not been integrated with technology systems such as Customer Relationship Management (CRM). This study also found that digital marketing performance tends to fluctuate and depends on promotional programs. Key challenges include high competition, price wars, limited digital literacy, and dependence on e-commerce platforms. Therefore, improving digital competency, innovative marketing strategies, and utilizing data-driven technology are necessary to support digital marketing success.